Correlation Between Sleep Disturbance and Agression on Childern With Autism Spectrum Disorder - Fauziah, Fany Nabila; Nining Febriyana; Mira Irmawati; Maria Beatriz Yazbek David Ramires (Jurnal Psikiatri Surabaya, 2025)
Introductions: Children with autism are a group of people with a pervasive developmental disorder characterized by abnormalities and/or developmental disabilities, marked by the presence of abnormalities in social interaction, communication, and limited and repetitive behavior. Children with Autism Spectrum Disorder have more sleep disturbances that correlate with the severity of autism symptoms, such as aggression. The aim of this study is to determine the relationship between sleep disturbances and aggression in children with autism at the Child Psychiatry Daycare Unit of Dr. Soetomo Regional General Hospital Surabaya. Methods: The research design used in this study is cross-sectional with a quantitative approach. Sampling was done using the total sampling method, resulting in 40 respondents. Sleep disturbance variables were measured using the Children’s Sleep Habit Questionnaire Abbreviated (CSHQ-A), and aggression variables were measured using the Modified Overt Aggression Scale (MOAS). Data were analyzed using Spearman’s correlation test. Results: The results showed a correlation coefficient of 0.841 with a significant p-value of < α 5% (0.05). Data analysis indicates that sleep disturbances in children with Autism Spectrum Disorder are strongly and linearly related to the level of aggression displayed. Conclusion: In conclusion, the more severe the sleep disturbances experienced by autistic children, the more severe the aggression displayed by children with Autism Spectrum Disorder.